Early Childhood Confidence is Based on The Implementation of Mushrooms in The House Apron Game in Kindergarten Aisyiyah Procot, District Tegal - Arini, Setya; Astuti, Henny Puji (Jurusan PGPAUD FIP UNNES, 2018)
Early childhood self-confidence is a deep conviction that the child possesses all his abilities and is aware of the deficiencies that exist in him that comes from the conscience and can do something useful for himself and others around him. Children who have confidence in carrying out their activities are always convinced that he is able to do the activity well and provide optimal results. The purpose of this study was to explain the differences in early childhood confidence based on the application of mushroom house apron games. This method in this research is quantitative res. Design True Experimental with type Posttest-Only Control Design. The population is all students kindergarten Aisyiyah be born, Tegal, with a sample of a kindergarten class experimental class B number of 20 children and a kindergarten class control class B and a number of 20 children. Data were obtained from the scale of confidence early childhood consists of 43 items that have been tested for validity and reliability. The scale is stuffed after treatment by investigators with the help of classroom teachers. Analysis of data using different test Independent Sample T-test. Based on the results of the study showed that, there are differences in early childhood confidence is based on the application of the mushroom house apron game. It is shown from the calculation of Independent Sample T-test, valuet of 3.467> t table 2,016 and sig (2-tailed) of 0.001 <0.05, and the mean of the experimental class at 129.8 while the mean control class is 108, 3 means that there are differences in early childhood confidence is based on the application of the mushroom house apron. The results also showed confidence in early childhood experimental class higher than the class of the control that does not use a mushroom house apron game.